Economics of Adaptation to Climate Change : Samoa - World Bank (Washington, DC, 2013)
Over the last two decades Samoa has suffered major damage from two cyclones in 1990-91, minor damage from a third cyclone in 2004, and an earthquake tsunami in 2009. Changes in the scale and impact of these types of natural disasters are likely to be important consequences of climate change for the country because the increases in sea level and in average sea surface temperatures will increase theintensity and damage from major storms. Other potential impacts are linked to changes in the weather patterns associated with El Niño Southern Oscillation (ENSO) events. The primary concern focuses on the impact on agriculture, especially in periods of lower precipitation following strong El Niño episodes.This study examines the consequences of an increase in average temperatures of up to 1°C by 2050 and up to 2.75°C by 2100 for the frequency and intensity of major cyclones that hit the islands. Estimates of the economic damage caused by storms in the past have been used to calibrate a damage function that yields an estimated increase in the expected value of economic damage as the peak wind speeds for storms with return periods of 10, 50, or 100 years rise over time. In this framework the key element of adaptation is to ensure that buildings and other assets are designed to standards that enable them to cope with the greater wind stresses and more intense precipitation associated with worse storms.